Kontribusi AMDAL Terhadap Pencegahan Pencemaran Lingkungan Pada Proyek Pembangunan - Rahmawati Rahmawati; Yolan Salma Hanifa; Cahya Darmawan (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
Environmental Impact Assessment (EIA) is an important instrument in ensuring that all development activities are carried out sustainably without neglecting environmental protection aspects. This study aims to examine the development of the concept, regulations, and role of EIA in environmental management through a literature review approach. Various scientific sources were used to explore how AMDAL has developed since the enactment of the initial provisions on environmental management to the latest regulations that strengthen AMDAL's position as an instrument for environmental licensing and supervision. The results of the study show that AMDAL has a strategic role in identifying potential negative impacts, formulating mitigation measures, and ensuring the integration of development policies and environmental sustainability. In addition, regulatory changes over time indicate an increase in the government's commitment to environmental protection through the improvement of the AMDAL mechanism. Thus, AMDAL has become an instrument that is not only normative but also operational in realizing environmentally conscious and sustainable development.